Determinan Keputusan Pembelian Produk Skincare Avoskin Beauty Melalui Minat Beli Sebagai Variabel Intervening - Sariyati; Guyub Nuryanto; Aulia Okta Rizki (Journal of Trends Economics and Accounting Research, 2024)
The aim of this research is to determine and analyze the influence of Celebrity Endorser, Electronic Word of Mouth (E-WOM), and Brand Image on Purchase Decisions for Avoskin Beauty Skincare Products through Purchase Interest as an Intervening Variable. This research method uses primary data which can be obtained by distributing questionnaires to consumers of Avoskin Beauty Skincare products with the help of Google form media. The test stages used are descriptive test, validity test, reliability test, structural model test (inner model), path coefficient test, mediation test (indirect effect). This research used a questionnaire instrument and processed data from 100 respondents. Sampling used a purposive sampling approach. The tool used is SmartPLS 3.2.9 software. The research results show that the Electronic Word of Mouth (E-WOM) variable and the Brand Image variable influence Purchase Interest as an Intervening variable. Meanwhile, the Celebrity Endorser variable has no effect on Purchase Interest as an Intervening variable. The Celebrity Endorser variable and the Brand Image variable influence purchasing decisions, while the Electronic Word of Mouth variable has no influence on purchasing decisions. The Purchase Interest variable has no effect on Purchase Decisions. The Celebrity Endorser variable and the Electronic Word of Mouth variable do not have a significant effect on Purchase Interest as an intervening variable on purchasing decisions. Meanwhile, the Brand Image variable has a significant effect on Purchase Interest as an Intervening variable on Purchase Decisions.